Implementasi Teknologi RFID dan Barcode dalam Optimalisasi Manajemen Inventaris Barang di Sektor Logistik - Edi Riesnandar; Imam Munajat Nuhartonosuro (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This research focuses on the challenges faced by the logistics sector in inventory management, where Radio Frequency Identification (RFID) and barcode technologies are seen as solutions to improve operational efficiency and accuracy. The purpose of this study is to explore the implementation of these two technologies in inventory management and analyze their impact on operational efficiency in the logistics sector. The research method used is a qualitative approach with in-depth interviews of five respondents working in logistics companies. Data collection was also carried out through field observations to identify the challenges and benefits experienced by companies in implementing RFID and barcode. The results of the study show that these technologies successfully improved data accuracy, reduced human errors, and accelerated the inventory recording process. Although challenges related to cost and device durability were identified, the implementation of RFID and barcode had a positive impact on inventory management, with RFID being more effective for large quantities of goods and barcode being more efficient for small quantities. The integration of both technologies into a hybrid system was seen as an optimal solution. The study suggests the need for enhanced infrastructure and staff training to optimize the application of these technologies in the logistics sector.